2020
DOI: 10.3892/ijmm.2020.4768
|View full text |Cite
|
Sign up to set email alerts
|

Long noncoding RNA KCNQ1OT1 contributes to tumor growth and activates Wnt/β‑catenin signaling in osteosarcoma by targeting the miR‑3666/KLF7 axis

Abstract: Osteosarcoma (OS) is a type of primary malignant cancer occurring in the bone and poses a threat to the lives of children and young adults. Long non-coding RNAs (lncRNAs) have been certified to play important roles in various human malignant tumors, including OS. lncRNA KcNQ1OT1 has been investigated in certain types of cancer; however, its role and molecular mechanisms in OS remain to be determined. In the present study, a high KcNQ1OT1 expression was detected in human OS tissues and cell lines. Moreover, pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 29 publications
0
15
0
Order By: Relevance
“…CCK-8 assays showed that RNAH19 knockdown increased miR-29a-3p expression and decreased LASP1 expression, which inhibited Saos2 and MG63 cell proliferation. Huang et al (2021) confirmed significantly inhibited proliferation and colony formation in U2OS and SAOS-2 cells after lncRNA KCNQ1OT1knockdown, as assessed by CCK-8 assay, colony formation assay, and western blot analysis. The authors suggested that lncRNA KCNQ1OT1 promoted tumor growth and activated the Wnt/ β catenin signaling pathway in OS by targeting the miR3666/ KLF7 axis.…”
Section: Introductionmentioning
confidence: 72%
“…CCK-8 assays showed that RNAH19 knockdown increased miR-29a-3p expression and decreased LASP1 expression, which inhibited Saos2 and MG63 cell proliferation. Huang et al (2021) confirmed significantly inhibited proliferation and colony formation in U2OS and SAOS-2 cells after lncRNA KCNQ1OT1knockdown, as assessed by CCK-8 assay, colony formation assay, and western blot analysis. The authors suggested that lncRNA KCNQ1OT1 promoted tumor growth and activated the Wnt/ β catenin signaling pathway in OS by targeting the miR3666/ KLF7 axis.…”
Section: Introductionmentioning
confidence: 72%
“…Li et al 28 reported TGFβ signaling pathway was involved in the progression and metastasis of osteosarcoma. Huang et al 29 revealed LncRNA KCNQ1OT1 promoted osteosarcoma growth by activating Wnt/β catenin signaling. Li et al 30 showed base excision repair and DNA replication in osteosarcoma can be blocked by inhibition of ATR‐Chk1 signaling.…”
Section: Discussionmentioning
confidence: 99%
“…The Kruppel-like factor 11 (KLF11) is expressed in a wide variety of tissues and controls proliferation, differentiation, and apoptosis ( Wang et al, 2021b ). MiR-3666/KLF7 axis, as the downstream target of KCNQ1OT1, regulate tumor growth ( Huang et al, 2021 ). The zinc finger protein YY1 belongs to the GLI-Kruppel class and is widely distributed throughout the human body ( Kwiatkowska et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%